Vegetative propagation of stevia [Stevia rebaudiana (Bertoni) Hemsl.] through stem cuttings - Smitha, G. R.; Umesha, K. (Journal of Tropical Agriculture, 2012)
Stevia rebaudiana (Bertoni) Hemsl. is a non-caloric bio-sweetener wherein seed propagation is difficult. Propagation of stevia through stem cuttings was evaluated under two environmental conditions (natural shade and greenhouse with intermittent mist) and four combinations of sand, soil, FYM, vermicompost, and coir dust, with growth regulator (IBA), bio-inoculants (Trichoderma viride), and cow’s urine treatments. Stem cuttings treated with T. viride, placed in soil, sand, and vermicompost rooting media (1:1:1) under greenhouse conditions recorded better shoot and root growth parameters, besides better field establishment (90%), over other treatment combinations.